Customer-service provider relationships: an empirical test of a model of service quality, satisfaction and relationship-oriented outcomes - (:unkn) unknown (MCB UNIV PRESS LTD, 1998)
The objective of this study was to empirically test a model of relationships among service quality, satisfaction and selected behavioural outcomes. Particular attention was paid to delineating the cognitive aspects of the service provider-consumer relationship from the affective, emotive factors. Using doctor-patient relationships in Turkey as the study setting, results of a LISREL analysis suggest that the affective aspects of satisfaction have more impact than cognitive factors on patients' propensity to continue the relationship. The most critical managerial implication of the study findings is that doctors need to place more emphasis on the functional (how it is done) aspects of care giving than the technical (what is done) ones.
Keywords: customer satisfaction; healthcare; service levels; service quality